Pengukuran Tingkat Partisipasi dan Interaksi dalam Grup WhatsApp serta Dampaknya terhadap Kemajuan Bahasa Arab pada Pelajar MA YUPPI Bandung - Aisyah, Khaeruni (Icon: Islamic Communication and Contemporary Media Studies, 2024)
The impact of the Covid-19 pandemic has brought about significant changes in human life, including in the education sector. To mitigate the spread of the virus, schools have been forced to transition to distance learning (DL). Distance learning can utilize various social media platforms such as WhatsApp (WA), Telegram, Instagram, Zoom application, or other platforms. The purpose of this research is to determine the level of participation and interaction in WhatsApp groups on the Arabic language proficiency of students at YUPPI Islamic High School in Bandung. Data from We Are Social in February 2023 shows that 88.7% of the total population of Indonesia are active WhatsApp users, making it the most frequently accessed social media application. This study takes its population from consumers in the Madrasah region, with a sample consisting of 150 respondents, a number calculated based on the Hair formula. Convenience sampling method was used in sample selection. Data were collected through survey method using a questionnaire as the research instrument. Data analysis was conducted using multiple linear regression statistical tests. SPSS version 23 was used as the analysis tool. The research findings indicate that partially, participation and interaction have a positive and significant impact on Arabic language proficiency.